Structural and Optical Properties of Co doped CdS Nanoparticles Synthesised by Chemical Method - Uday Ali Sabeeh Al-Jarah / Hadeel Salih Mahdi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Constructed using the sol gel technique, the CdS nanoparticles contain cobalt. Scientists used X-ray diffraction (XRD) analysis to determine the properties of the particles they collected. The structural characterization results demonstrate the synthesis of impurity-free, Co-doped CdS nanoparticles in a single phase. We have shown and discussed the UV-VIS spectrophotometer-recorded optical absorption spectra of the doped sample in the 350–800 nm wavelength range. According to the Tauc relationship, the energy band gap is 2.46 eV. Potentially useful uses for co-doped CdS include photocatalysis, sensors, and solar cells.